QUANTITATIVE ANALYSIS OF CHORIOCAPILLARIS ALTERATIONS IN SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY-ANGIOGRAPHY DURING RADIATION RETINOPATHY. Issue 10 (October 2022) - Gilli, Christelle; Kodjikian, Laurent; Loria, Olivier; Jabour, Charles; Rosier, Laurence; Nhari, Maxime; Nguyen, Anh Minh; Herault, Joël; Thariat, Juliette; Salleron, Julia; Mathis, Thibaud
Abstract : Supplemental Digital Content is Available in the Text. We evaluated choriocapillaris flow voids area following proton beam irradiation for uveal melanoma using swept-source optical coherence tomography-angiography. We showed that choriocapillaris alterations occur in the early stages of radiation retinopathy and could be a predictive marker of progression to higher grades. Abstract : Purpose: To evaluate choriocapillaris alterations following proton beam therapy irradiation using swept-source optical coherence tomography-angiography, and to assess their correlation with the grade of radiation retinopathy (RR). Methods: Eyes with uveal melanoma evaluated before and after irradiation with proton beam therapy were included, as well as the healthy fellow eye. The gradation of RR was based on a previously published classification. Choriocapillaris flow voids area was analyzed using Phansalkar thresholding. Retinal vascularization was described by foveal avascular zone (FAZ) perimeter, FAZ area, FAZ circularity index, and percentage of nonperfusion area (PAN) in the superficial capillary plexus (SCP) or deep capillary plexus. Results: A total of 157 eyes of 83 patients were analyzed. Overall, there was a significant difference between the control group, the uveal melanoma before proton beam therapy group, and the grades of RR in the uveal melanoma after proton beam therapy group for FAZ perimeter ( P < 0.001), FAZ area ( P < 0.001), FAZ-circularity index ( P < 0.001), PAN-SCP ( P < 0.001), PAN-deep capillary plexus ( P < 0.001), and choriocapillaris flow voids area ( P < 0.001). Moreover, choriocapillaris flow voids area was significantly increased in the early stages of RR ( P = 0.003) and was further significantly correlated with FAZ perimeter ( P < 0.001), FAZ area ( P < 0.001), FAZ-circularity index ( P = 0.010), PAN-SCP ( P < 0.001), and PAN-deep capillary plexus ( P < 0.001). Conclusion: Quantitative optical coherence tomography-angiography alterations in the choriocapillaris microvascularization are an early biomarker of RR and are correlated to the severity of the disease.